2005
DOI: 10.1021/jf0504770
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vine Vigor on Grape (Vitis viniferaL. Cv. Pinot Noir) and Wine Proanthocyanidins

Abstract: The relationships between variations in grapevine (Vitis vinifera L. cv. Pinot noir) growth and resulting fruit and wine phenolic composition were investigated. The study was conducted in a commercial vineyard consisting of the same clone, rootstock, age, and vineyard management practices. The experimental design involved monitoring soil, vine growth, yield components, and fruit composition (soluble solids, flavan-3-ol monomers, proanthocyanidins, and pigmented polymers) on a georeferenced grid pattern to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
168
7
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(221 citation statements)
references
References 33 publications
36
168
7
3
Order By: Relevance
“…However, for the vine yield variable, the Pearson correlations were poor and ANOVA test showed that high vigor vines yielded lower or similar than medium vigor vines. This could be explained by an excess of vigor on some of those vines, which originated a poor fruit setting and/or reduced bud fruitfulness, as observed by Cortell et al (2005).…”
Section: Discussionmentioning
confidence: 96%
“…However, for the vine yield variable, the Pearson correlations were poor and ANOVA test showed that high vigor vines yielded lower or similar than medium vigor vines. This could be explained by an excess of vigor on some of those vines, which originated a poor fruit setting and/or reduced bud fruitfulness, as observed by Cortell et al (2005).…”
Section: Discussionmentioning
confidence: 96%
“…These rootstocks showed almost a two-fold increase in pruning weight from 2011 to 2012. The high increase in plant vigor may have decreased the skin proanthocyanidin mean degree of polymerization in shaded fruits (Cortell et al, 2005). However, it is important to highlight that the values of anthocyanin and total phenolic for all seasons and rootstocks remained within the expected range for quality wine, i.e.…”
Section: Rootstock Effects On Grape Compositionmentioning
confidence: 94%
“…Variations in grapevine vigour commonly correlate with fruit/wine characteristics on a site-specific level elsewhere (e.g. Cortell et al, 2005;Trought et al, 2008), so the variation in grapevine trunk circumference observed at these study sites likely contributes to differences in grape characteristics. Yield can vary up to 10-fold in the same vineyard block, and this variation in yield has associated quality implications (Bramley, 2001).…”
Section: Vine Vigourmentioning
confidence: 93%
“…These localised variations in even small vineyard blocks can in turn show differences in grape quality parameters (e.g. Cortell et al, 2005;Trought et al, 2008). If blocks are uniformly managed, changes in soil properties or local topography may contribute to variations in vine trunk circumference.…”
mentioning
confidence: 99%